Analisis Faktor Penyebab dan Dampak Pernikahan Dini bagi Kesejahteraan Keluarga - tajuk, Tajuk Sinemahate (JAROW: Journal of Ar-Raniry on Social Work, 2024)
The problem of Early Marriage is caused by various factors and has many positive and negative impacts. This study aims to determine the causes, impacts, and perspectives of community leaders regarding Early Marriage. Using descriptive qualitative research with interview data collection techniques, observation, and documentation of 9 informants, the results of the study showed that there are 4 factors of early marriage, namely the factor of getting pregnant outside of marriage, the factor of one's own will, economic factors, and customary factors or hereditary habits. The impacts of Early Marriage are economic limitations due to not having a decent job, dropping out of school due to early marriage, and disputes in the household. And the perspective of community leaders on Early Marriage is partly very regrettable and some community leaders are no longer surprised by Early Marriage because since the time of their ancestors Early Marriage has often occurred.